2016
DOI: 10.1159/000448048
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Controlled Growing Rod in Early-Onset Scoliosis: A Minimum of 2-Year Follow-Up

Abstract: Purpose: The magnetically controlled growing rod technique decreases complications, costs, and loss of functionality by avoiding successive surgical corrections every 6 months in patients with early-onset scoliosis. However, only a few studies have presented clinical experience with the magnetically controlled growing rod. In this study we aimed to present our single-center experience in patients with early-onset scoliosis who underwent the magnetically controlled growing rod technique and follow-up for at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…While three studies reported no complications in their combined 15 MCGR patients. 36,37,40 43 reported one revision in three patients for hook pull-out. Our MCGR cohort is so far the largest reporting on only idiopathic EOS patients and our complication rates seem to fall in between these reports.…”
Section: Discussionmentioning
confidence: 99%
“…While three studies reported no complications in their combined 15 MCGR patients. 36,37,40 43 reported one revision in three patients for hook pull-out. Our MCGR cohort is so far the largest reporting on only idiopathic EOS patients and our complication rates seem to fall in between these reports.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are similar to previously published studies regarding the age of child at implantation, degree of curve, and length of follow-up. Previous studies report a MCGR mechanical failure rate (all causes) of 0%–75% [ 3 , 19 , 20 ], and there have been two specific actuator pin failures published as a case report [ 21 ]. In their revised quantitative analysis of four papers (one of which was unpublished) [ 4 , 22 , 23 ], the NICE external assessment center reported five MCGR device failures in 80 patients (6%).…”
Section: Discussionmentioning
confidence: 99%
“…The distraction frequency was 1–2 months reported in studies by Cheung et al [24], Hickey et al [14], and Teoh et al [35]. The distraction frequency was 3–6 months in studies conducted by La Rosa et al [34], Yilmaz et al [36], Nnadi et al [39], and Yoon et al [37]. The average postoperative distracted length was 28.3 mm (range of follow-up, 23–61 months) in the present systematic review.…”
Section: Resultsmentioning
confidence: 90%